(untitled) (TERRA LATINOAMERICANA, 2026)
Cherry tomato (Solanum lycopersicum var. cerasiforme) is a crop of great economic importance due to its high demand for fresh consumption and the benefits of its bioactive compounds for human health. However, the excessive use of agrochemicals in its cultivation has generated negative effects on the environment and on human and animal health. Therefore, alternatives are being sought to reduce these effects, such as plant biostimulant microorganisms. The objective of this study was to evaluate the effect of Trichoderma harzianum, Bacillus subtilis, and Azospirillum brasilense as biostimulants on quality and yield parameters of greenhouse-grown cherry tomato. A completely randomized experimental design with five treatments and 44 replicates per treatment was used: T1 = 100% chemical fertilizer (CF); T2 = 50% CF + T. harzianum; T3 = 50% CF + B. subtilis; T4 = 50% CF + A. brasilense; and T5 = 50% CF + consortium (T. harzianum, B. subtilis, and A. brasilense). Morphological and physicochemical variables, as well as bioactive compounds of the fruit, were evaluated. The results were subjected to analysis of variance (ANOVA) and Tukey’s test (p < 0.05) using STATISTICA v. 12.0 for Windows. Statistical analysis showed significant differences among treatments, with plants in Treatment 4 (50% CF + A. brasilense) exhibiting the highest values for bunch weight, fruit weight, equatorial and polar diameter, total soluble solids (TSS), vitamin C, lycopene, β-carotene, color, and yield. These results suggest that inoculation with Azospirillum brasilense combined with a reduced dose of chemical fertilizer may represent an alternative strategy to increase the quality and yield of cherry tomato under greenhouse conditions.